Factors determining the operational self-sufficiency of microfinance institutions - Nejra Hadžiahmetović (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2021)
The main aim of this paper is to explore the factors determining Microfinance institutions (MFIs) self-sufficiency. The data on selected variables for this research were obtained from the public MIX Market Database and cover the year of 2017. The empirical model is constructed with application of a Principal Component Analysis (PCA) and Logistic regression analysis. Sample is consisted of 342 MFIs from all around the world, with 21 independent variables grouped into eight factors/components, and OSS (operational self-sufficiency) as dependent variable. The obtained results suggest that higher revenue and MFIs profitability combined with decrease of credit risk lead to higher probability of MFI to be self-sufficient. These results also confirm widespread belief that MFIs will not be able to achieve their social goals without achieving sustainable profitability. In addition, results also confirm importance of MFIs core mission as with increase in outreach, probability of MFIs achieving self-sustainability also increases.
Keywords: G21; L31; 330; determinants; exploratory factor analysis; logistic regression; microfinance institutions; operational self-sufficiency